The Building of Pulsed NQR/NMR Spectrometer - Preeti Hemnani; A. K. Rajarajan; Gopal Joshi; S. V. G. Ravindranath (Institute of Advanced Engineering and Science, 2018)
NQR spectrometer designed is composed of four modules; Transmitter, Probe, Receiver and computer controlled (FPGA & Software) module containing frequency synthesizer, synchronous demodulator, pulse programmer and display. The function of the Transmitter module is to amplify the RF pulse sequence to about 200 W power level into the probe (50 Ohm) which is a parallel resonance circuit with a tapped capacitor. The probe excites the nucleus and picks-up the signal emitted from the nuclei. The nuclear signal at the same frequency as the excitation, which is typically in the range of a few microvolts is amplified, demodulated and filtered (1 kHz to 100 kHz) by receiver module. 14N NQR, 1H and 2H NMR signals are observed from the spectrometer.As the SNR of NQR signal is very low, NQR signal processing based on Adaptive Line Enhancement is presented.